Design and Experimental Demonstration of Wavelength‐Selective Metamirrors on Sapphire Substrates - Mariia Matiushechkina; Andrey B. Evlyukhin; Radu Malureanu; Vladimir A. Zenin; Torgom Yezekyan; Andrei Lavrinenko; Sergey I. Bozhevolnyi; Boris N. Chichkov; Michèle Heurs (Advanced Photonics Research)
The increasing demand for novel mirror coating designs for new generation of gravitational wave detectors is stimulating significant research interest in investigations of reflective properties of metasurfaces. Given this strong interest, this article details a systematic methodology for fabricating reflecting metasurfaces (metamirrors) designed to operate at target wavelengths of 1064 or 1550 nm. The proposed metasurfaces consist of silicon cylindrical nanoparticles placed on a sapphire substrate. First, the dimensional parameters of the structures are thoroughly selected through numerical simulations combined with material characterization. The configurations are subsequently analyzed analytically to reveal the mirror effect, which arises from the excitation of electric and magnetic dipole moments. Following this, the metasurfaces are fabricated and experimentally characterized, demonstrating reflectivity exceeding 95% around the design wavelengths, which is in good agreement with theoretical predictions. Overall, the work demonstrates the feasibility and detailed methodology for the fabrication of thin, lightweight metamirrors capable of achieving near‐perfect reflectivity at the specified target wavelengths.